Justice, Equality, and Indonesian Labor Law: Navigating Humanitarian Challenges in the Workplace - Nurhayati, Tri; Ismoyoputro, Raden Lungid (Universitas Islam Negeri Walisongo Semarang, 2024)
The increasing complexity of labor relations in Indonesia has led to widespread inequality, discrimination, and human rights violations in the workplace. These conditions underscore the urgent need for stronger legal protections to ensure justice and equality for all workers. This article examines the humanitarian challenges arising from the expanding labor force, which has weakened workers’ bargaining power and increased their vulnerability to exploitation by employers. As the primary policymaker, the government bears the constitutional obligation to protect workers and uphold human rights, as mandated by the 1945 Constitution of the Republic of Indonesia. Employing a non-doctrinal research approach with a normative perspective, this study utilizes documentation and literature as primary data sources. The findings reveal that equality and justice within Indonesia’s labor system have not been fully realized. The legal transition from Law No. 13 of 2013 on Manpower to Law No. 6 of 2023 on Job Creation further underscores disparities in labor relations, as workers continue to face structural vulnerabilities. Common forms of injustice include discrimination in recruitment and workplace practices, harassment, intimidation, labor exploitation, violations of occupational health and safety standards, unfair wage systems, and neglect of workers’ rights during termination of employment. These findings emphasize the urgent need for comprehensive labor law reform to ensure fairness, dignity, and the protection of fundamental rights for all workers. Meningkatnya kompleksitas hubungan industrial di Indonesia telah menimbulkan ketimpangan, diskriminasi, dan pelanggaran hak asasi manusia di lingkungan kerja. Kondisi tersebut menegaskan urgensi penguatan perlindungan hukum guna menjamin keadilan dan kesetaraan bagi seluruh pekerja. Artikel ini mengkaji tantangan kemanusiaan yang muncul akibat meningkatnya jumlah tenaga kerja, yang berimplikasi pada melemahnya posisi tawar pekerja dan meningkatnya kerentanan terhadap eksploitasi oleh pemberi kerja. Sebagai pembuat kebijakan utama, pemerintah memiliki kewajiban konstitusional untuk melindungi pekerja dan menegakkan hak asasi manusia sebagaimana diamanatkan dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Dengan menggunakan pendekatan penelitian non-doktrinal melalui perspektif normatif, studi ini memanfaatkan dokumentasi dan kajian pustaka sebagai sumber data utama. Hasil penelitian menunjukkan bahwa prinsip kesetaraan dan keadilan dalam sistem ketenagakerjaan Indonesia belum sepenuhnya terwujud. Peralihan regulasi dari Undang-Undang No. 13 Tahun 2013 tentang Ketenagakerjaan ke Undang-Undang No. 6 Tahun 2023 tentang Cipta Kerja semakin menegaskan adanya disparitas dalam hubungan industrial, di mana pekerja masih menghadapi kerentanan struktural. Bentuk-bentuk ketidakadilan yang umum terjadi meliputi diskriminasi dalam rekrutmen dan praktik kerja, pelecehan, intimidasi, eksploitasi tenaga kerja, pelanggaran standar keselamatan dan kesehatan kerja, sistem upah yang tidak adil, serta pengabaian hak-hak pekerja saat pemutusan hubungan kerja. Temuan ini menegaskan perlunya reformasi hukum ketenagakerjaan yang komprehensif untuk menjamin keadilan, martabat, serta perlindungan hak-hak fundamental bagi seluruh pekerja. Keywords: Human Rights, Justice, Equality, Labor Law, Humanitarian Challenges.